Asymmetric spectral filtering for spectral-overlap suppression and differential phase-contrast reconstruction in spatial harmonic imaging - Hyunwoo Lim; Jonghyeok Lee; Seohee Han; Hyosung Cho (Physics in Medicine & Biology, 2026)
Abstract Objective. Spatial harmonic imaging (SHI) enables single-shot multi-contrast X-ray imaging, including dark-field imaging (DFI) and differential phase-contrast imaging (DPCI). However, spectral overlap between the first-harmonic band and adjacent spectra can produce wraparound artifacts and structural distortions. Asymmetric spectral filtering (ASF) has recently been proposed to suppress such artifacts in SHI-based DFI, but its effect on the first-harmonic signal and its applicability to DPCI remain unclear. This study aimed to analyze the effect of ASF on the first-harmonic signal and systematically investigate its applicability to DPCI, with particular emphasis on the delineation of small calcification-like inclusions in a breast-equivalent phantom and soft-tissue boundaries and internal structures in a biological specimen. Approach. The effect of ASF on the first-harmonic signal was analyzed using a first-order approximation. Monte Carlo simulations and X-ray imaging experiments were conducted using symmetric filtering, low-frequency-only filtering, and ASF for comparison. Main results. In simulations of a breast-equivalent phantom containing small hydroxyapatite inclusions, ASF increased the edge-based signal-to-noise ratio (ESNR) by a factor of 1.96 compared with symmetric filtering. In fish specimen experiments, ASF achieved a 2.46-fold improvement in ESNR and enabled clearer delineation of boundaries and internal structures. In the experiment involving a banana specimen with an inserted pencil lead, ASF yielded the highest ESNR and clearest target delineation. Significance. These results suggest that ASF reduces spectral-overlap artifacts while allowing phase-related information relevant to DPCI to remain reflected in the reconstructed phase. The resulting improvements in the delineation of small calcification-like inclusions in a breast-equivalent phantom and soft-tissue boundaries and internal structures in a biological specimen support the biomedical relevance of ASF for single-shot SHI-based DPCI under the investigated low-energy and small-specimen conditions.